Risco-País e Investment Grade: contribuição do serviço social para sua desmistificação - Borgianni, Elisabete (2008)
This paper examines, based on the principles of the Marxist theory, the Country-Risk rating as well as the risk ratings developed by specialized agencies. We show how mystified the social relations which characterize the monopolistic stage of capital are presented. The main finding is that, although the Brazilian government refers to investment grade as an achievement of the society as a whole, such ratings just consider the needs for capital reproduction, mainly in its financial and rentist form, never focusing on the true welfare of the working class. We show that, instead, for a country to reach the best country risk ratings, it needs to follow a macroeconomic agenda that implies social rights suppression through budgetary restraints of social policies. We also maintain that these mystification processes, typical of capitalist production, may be uncovered through critical analysis and a political attitude to oppose this form of social organization based on private property of the main means of production. We also examine the critical-analytical and political-organizational potential the Brazilian Social Work has developed in the last years, and defend the idea that this potential enables it to play a stronger and more meaningful role in the debate about the course of the economical and social policy of the country. Such role may be stimulated by creating a system to monitor violation of human rights - to be implemented by or in the Federal and Regional Social Work Boards - , to counteract ratings that only measure risks to capital, such as Country-Risk